Optimization of ultraviolet/ozone (UVO3) process conditions for the preparation of gelatin coated polystyrene (PS) microcarriers - Mohd Azmir, Arifin; Mel, Maizirwan; Swan, Sia Yiik; Nurhusna, Samsudin; Hashim, Yumi Zuhanis Has-Yun; Mohd Salleh, Hamzah (Taylor & Francis Group, 2022)
The aim of this study was to develop gelatin coated polystyrene (PS) microcarriers with good cell adhesion and proliferation properties. PS microspheres, prepared using oil-in water (o/w) solvent evaporation method, were loaded with oxygen containing functional groups using an ultraviolet/ozone (UVO3) system. Using water-soluble carbodiimide chemistry, gelatin was subsequently immobilized on UVO3 treated PS microspheres. The amount of immobilized gelatin was found to be directly proportional to the surface carboxyl (COOH) concentration on PS microspheres. Face Centered Central Composite Design (FCCD) was employed to optimize the process conditions of UVO3 treatment to maximize the surface COOH concentration on PS microspheres for allowing higher gelatin immobilization. Statistical results revealed that, the optimized process conditions were ozone flow rate of ∼64,603 ppm, exposure time of ∼60 minutes and sample amount of 5.05 g. Under these conditions, the surface COOH concentration on PS microspheres was ∼1,505 nmol/g with the corresponding amount of immobilized gelatin was ∼2,725 µg/g. Characterization analyses strongly suggest that the optimized UVO3 treatment and successive gelatin immobilization have successfully improved surface wettability and dispersion stability of PS microspheres. Moreover, gelatin coated PS microcarriers were also proven as able to support the growth of CHO-K1 cells in high cell density culture.